Outer Banks Tourists' Preferences, Sensitivities, and Environmental Perceptions: A Case Study of Cape Hatteras National Seashore - McSherry, Logan M. (East Carolina University, 2018)
Tourism is the driving economic force for North Carolina's Outer Banks, attracting millions of visitors every year. However, through the combined effects of increased human activity and development, storms, sea level rise, and climate change, portions of the island chain are disappearing. This study seeks to better understand why visitors choose the Outer Banks, how aware and concerned they are about environmental changes occurring there, and how that may affect their beach destination choice in the future. To address these questions, a survey of 137 visitors at Cape Hatteras National Seashore was undertaken. The relative sensitivity to seven environmental variables is considered and differences in perception among local and non-local beachgoers are compared. Analyses of scores and responses to survey questions show that scenery and uncrowded beaches are the primary reasons for choosing the Outer Banks, followed closely by location and accessibility. Visitors appear to be generally conscious of the changing environment there, with a majority of respondents saying they were aware of environmental changes at the Outer Banks prior to being surveyed. However, only half of respondents indicate experiencing effects from these changes during their visit. As such, respondents expressed environmental changes as having little to no effect on their decision to return, with over 95% claiming they will still recommend the Outer Banks and revisit in the future. For many, the fact that the Outer Banks remains relatively undeveloped compared to other East Coast beaches constitutes enough reason to return in spite of other changes.
Keywords: Environmental Perception; Environmental Change; Marine and Coastal Resources; Tourism Geography; Coastal Tourism; Outer Banks; Tourists--North Carolina--Hatteras, Cape--Attitudes; Environmental impact analysis--North Carolina--Hatteras, Cape; Social sciences--North Carolina--Hatteras, Cape